Judicial engagement: lessons from problem solving courts - McIvor, Gill (2012)
This article critically assesses the development of judicial involvement in offender management drawing both on international literature and on experiences of courts in the UK that have adopted 'problem-solving' approaches that aim to enhance the 'therapeutic' potential of court processes